New Perspectives in Magnesium Research
DOI: 10.1007/978-1-84628-483-0_19
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium: Forgotten Mineral in Cardiovascular Biology and Atherogenesis

Abstract: In this review, a rationale is presented for how hypercholesterolemia, hypertension, diabetes mellitus (DM), end-stage renal disease (ESRD), prolonged stress, and exposure to magnesium (Mg)-wasting drugs can lead to atherosclerosis, ischemic heart disease, and stroke. The data, accumulated so far, indicate that Mg defi ciency caused either by a poor diet or errors in Mg metabolism may be a missing link between diverse cardiovascular risk factors and atherogenesis. Early data from our laboratory and others indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
89
0

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(98 citation statements)
references
References 87 publications
8
89
0
Order By: Relevance
“…Most such diets in the U.S.A. show that 60 -80% of Americans are consuming only 185-235 mg Mg/day [4][5][6]. Low Mg content in drinking water found in areas of soft water and Mg-poor soil, is associated with high incidences of ischemic heart disease, severe atherosclerosis, coronary vasospasm, hypertension, hyperlipidemia, diabetes, and sudden cardiac death [4,[7][8][9][10][11][12][13][14]. Both animal and human studies have shown an inverse relationship between dietary intake of Mg and atherosclerosis [4,13,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most such diets in the U.S.A. show that 60 -80% of Americans are consuming only 185-235 mg Mg/day [4][5][6]. Low Mg content in drinking water found in areas of soft water and Mg-poor soil, is associated with high incidences of ischemic heart disease, severe atherosclerosis, coronary vasospasm, hypertension, hyperlipidemia, diabetes, and sudden cardiac death [4,[7][8][9][10][11][12][13][14]. Both animal and human studies have shown an inverse relationship between dietary intake of Mg and atherosclerosis [4,13,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Low Mg content in drinking water found in areas of soft water and Mg-poor soil, is associated with high incidences of ischemic heart disease, severe atherosclerosis, coronary vasospasm, hypertension, hyperlipidemia, diabetes, and sudden cardiac death [4,[7][8][9][10][11][12][13][14]. Both animal and human studies have shown an inverse relationship between dietary intake of Mg and atherosclerosis [4,13,[15][16][17][18][19]. The myocardial level of Mg has consistently been observed to be lower in subjects dying from ischemic heart disease and sudden cardiac death in soft water areas [4,7,9,11,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations